Plasticity and geotechnics - Yu, Hai-Sui (Springer, 2006)
Introduction -- Elements of continuum mechanics -- Foundations of the theory of plasticity -- General elastic-plastic theorems -- Perfect plasticity -- Isotropic hardening and critical state theory -- Multi-surface and bounding surface plasticity -- Non-coaxial plasticity -- Plasticity without a prior yield criterion -- Rigorous analysis of elastic-plastic problems -- Slip line analysis -- Limit analysis -- Shakedown analysis -- Finite element analysis.
Literaturangaben
Keywords: Plasticity; Soil mechanics; Bodenmechanik; Plastizität; Gesteinsmechanik; Mathematisches Modell